Actuator Surface Model and Blade Resolved Simulations of an Attack Reconnaissance Class Rotor in Hover and Forward Flight - Coyle, A.; Thornber, B. (My University, 2023)
Two novel simulation methodologies were used to compute the forces acting upon the rotor of an Attack Reconnaissance Class (ARC) helicopter in both hover and forward flight. The first of these is the Actuator Surface Model (ASM), a hybrid Computational Fluid Dynamics (CFD) technique that allows for complex simulations of rotors at a markedly lower computational cost than traditional blade-resolved methods without a significant reduction in accuracy. Blade resolved calculations were performed using The University of Sydney code Flamenco, which employs a combination of very high order accurate schemes with a novel Radial Basis Function (RBF) mesh motion method. This enabled high mesh quality to be maintained after changing the pitch of the blade. The ASM and Flamenco were validated against each other, as well as published experimental and simulation datasets. In hover, excellent agreement is found between all solvers. The ASM was also used to perform forward flight calculations, producing results accurate to the validation dataset.
Keywords: Aerodynamics